Discussion: The Denomination of Foreign Trade Contracts Once Again - Levich, Richard M. (Journal of Financial and Quantitative Analysis, 1980)
Richard M. Levich, Discussion: The Denomination of Foreign Trade Contracts Once Again, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 4, Proceedings of 15th Annual Conference of the Western Finance Association, June 19-21, 1980, San Diego, California (Nov., 1980), pp. 945-947